Functional organization of the cerebral cortex - Concha Bartolini, Mauricio (Medicina UPB, 1987)
The most recent advances in the understanding of the organization of the cerebral cortex permit to e valuate clinically the functional status os specific zones in the brain, without the need of ex, pensive paraclinical procedures - many of thorn harmful, besides. In this paper, in a necessarily brief way, and as a clinical aid for medical students as well as for physicians without specific training in neurosciences, some practical aspects of the cerebral organization are emphasized.